2004
DOI: 10.1086/380414
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Matrix Metalloproteinases byBorrelia burgdorferivia Toll‐Like Receptor 2 in Monocytes

Abstract: Regulation of secretion of matrix metalloproteinase (MMP) underlies the basis of numerous physiological and pathological processes in multicellular organisms. The Toll receptor family, which is conserved from Drosophila species to humans, mediates pattern recognition of a diversity of ligands involved in morphogenesis and innate immunity. Here, we show that secretion of MMP-9 is selectively induced through Toll-like receptor (TLR) 2 in human and murine monocytic cells stimulated with Borrelia burgdorferi. Secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 49 publications
6
46
0
1
Order By: Relevance
“…Not only do these enzymes naturally occur in the blood circulation, but they are also expressed as a result of the interaction between host cells and B. burgdorferi. There have been several reports showing that astrocytes (69), chondrocytes (33,53), and monocytes (26,27) express MMPs in response to B. burgdorferi. These reports have also shown that the interaction of B. burgdorferi with host cells leads to the activation of plasminogen that activates these MMPs, thus facilitating the degradation of the extracellular matrix.…”
mentioning
confidence: 99%
“…Not only do these enzymes naturally occur in the blood circulation, but they are also expressed as a result of the interaction between host cells and B. burgdorferi. There have been several reports showing that astrocytes (69), chondrocytes (33,53), and monocytes (26,27) express MMPs in response to B. burgdorferi. These reports have also shown that the interaction of B. burgdorferi with host cells leads to the activation of plasminogen that activates these MMPs, thus facilitating the degradation of the extracellular matrix.…”
mentioning
confidence: 99%
“…TLR-2 has been shown to be involved in B. burgdorferi induction of some, but not all, MMPs from human monocytes (14). We have shown previously that B. burgdorferi induces MMP-1 and MMP-3 from HC cells and that this induction involves MAPK (ERK1/2, p38 MAPK, and JNK) pathways that could potentially be activated through TLR-2 signaling (30 -33).…”
Section: Role Of Tlr-2 In B Burgdorferi-induced Expression Of Mmp-1 mentioning
confidence: 86%
“…However, the receptors that are responsible for activation of these signaling pathways in joint tissue remain unknown. Gebbia et al (14) have shown previously that TLR-2 is involved in the induction of MMP-9 from monocytes, but does not appear to be involved in the induction of MMP-1. MMP-9 has not been found to be elevated in the joints of humans or mice with Lyme arthritis (10).…”
Section: Identification Of a Tlr-independent Pathway For Borrelia Burmentioning
confidence: 96%
“…Its upregulation in B. burgdorferi-stimulated macrophages is probably worthy of further investigation. MMP9, a granulocyte-secreted type IV collagenase (88), has been shown previously to be induced by B. burgdorferi in both human and murine monocytes in a TLR2-dependent manner (37,38). MMP9 is also upregulated in erythema migrans lesions of Lyme disease patients (99,100) and in joints of Lyme diseasesusceptible mice (7).…”
Section: Discussionmentioning
confidence: 97%